Conflicts at the Intersection of Nature, Well-being, and Social Relationships in Wilde's The Devoted Friend - Mendrofa, Melania; Sudiman, Jovanna Mazella (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This study investigates the complex interplay between nature, well-being, and social relationships, focusing on understanding how social dynamics can undermine the positive effects of nature on individual well-being. The research seeks to answer the primary question: How do social relationships influence the impact of nature on well-being? Using Oscar Wilde’s short story, The Devoted Friend, as a case study, this research employs descriptive textual analysis to examine the character of Hans and his relationship with nature, highlighting the harmful effects of social exploitation. The concept of intersectionality is applied to analyze how overlapping social pressures within nature-related experiences can negatively affect well-being. Key findings reveal that while nature-related activities, such as gardening, are widely recognized for their psychological benefits, the influence of toxic social interactions can erode these benefits, leading to submissive behaviors and well-being deterioration. The research concludes that addressing these social challenges is crucial for fully realizing the positive impacts of nature. The study’s implications suggest the need for a deeper understanding of how social dynamics intersect with environmental experiences, calling for strategies to mitigate the adverse effects and enhance well-being.Abstrak Penelitian ini menyelidiki keterkaitan kompleks antara alam, kesejahteraan, dan hubungan sosial, dengan fokus pada pemahaman bagaimana dinamika sosial dapat merusak efek positif alam terhadap kesejahteraan individu. Penelitian ini berupaya menjawab pertanyaan utama: Bagaimana hubungan sosial mempengaruhi dampak alam terhadap kesejahteraan? Dengan menggunakan cerita pendek karya Oscar Wilde, The Devoted Friend, sebagai studi kasus, penelitian ini menerapkan analisis tekstual deskriptif untuk meneliti karakter Hans dan hubungannya dengan alam, menyoroti dampak merugikan dari eksploitasi sosial. Konsep interseksionalitas diterapkan untuk menganalisis bagaimana tekanan sosial yang saling tumpang tindih dalam pengalaman yang berkaitan dengan alam dapat berdampak negatif pada kesejahteraan. Temuan utama mengungkapkan bahwa meskipun kegiatan yang terkait dengan alam, seperti berkebun, secara luas diakui memberikan manfaat psikologis, pengaruh interaksi sosial yang beracun dapat merusak manfaat tersebut, yang pada akhirnya mengarah pada perilaku tunduk dan penurunan kesejahteraan. Penelitian ini menyimpulkan bahwa mengatasi tantangan sosial ini sangat penting untuk mewujudkan dampak positif alam secara penuh. Implikasi penelitian ini menunjukkan perlunya pemahaman yang lebih mendalam tentang bagaimana dinamika sosial beririsan dengan pengalaman lingkungan, dan menyerukan adanya strategi untuk mengurangi dampak negatif serta meningkatkan kesejahteraan.Kata Kunci: Interseksionalitas, Kesejahteraan, Alam, Hubungan sosial